Frontispiece: A Layered Tin Bismuth Selenide with Three Different Building Blocks that Account for an Extremely Large Lattice Parameter of 283 Å. Issue 47 (21st August 2020) - Nentwig, Markus; Eisenburger, Lucien; Heinke, Frank; Souchay, Daniel; Oeckler, Oliver
Abstract : The synergism of synchrotron radiation and transmission electron microscopy (STEM‐HAADF) enabled the structural analysis of a new tin bismuth selenide with an extraordinarily large lattice parameter of 283 Å. Sn2.8(4) Bi20.2(4) Se27 is built up from three types of layers forming a long‐periodic 150 R stacking sequence. The structure model is perfectly confirmed by STEM with atomic‐resolution chemical mapping. More information can be found in the Communication by O. Oeckler et al. on page 10676 ff .